Commuting patterns and bicycle level of traffic stress (LTS): Insights from spatially aggregated data in Franklin County, Ohio. (June 2020) - Wang, Kailai; Akar, Gulsah; Lee, Kevin; Sanders, Meredyth
Abstract: This study analyzes the relationships between bicycle network design and commute mode shares in Franklin County, Ohio. We first adopt the bicycle level of traffic stress (LTS) criteria to measure bicycle network design. Then, we develop a fractional multinomial logit model to simultaneously estimate the determinants of the shares of commuters who regularly go to work by carpooling, riding public transit, bicycling, and walking. The analytical results show that increasing the proportion of low-stress road segments (LTS 2) is statistically significant and positively associated with the share of bicycle commuters at the census block group level. However, we do not observe a significant relationship between the proportion of very low-stress road segments (LTS 1) and the share of bicycle commuters. This study suggests that social and cultural relevant factors are more important predictors of reductions in automobile use as compared to those factors representing road conditions. Highlights: This study conducts a bicycle level of traffic stress (LTS) analysis in Franklin County, Ohio. A fractional multinomial logit model is estimated to simultaneously model the correlates of four types of commute mode choices. Increasing the percentage of low-stress road segments (LTS 2) can be an effective treatment to promoting the share of bicycle commuters.